Disasters as contingent events volcanic eruptions, state advisories, and public participation in the twentieth-century Philippines - Aguilar, Filomeno V., Jr (Philippine studies : historical and ethnographic viewpoints, 2016)
"By revisiting the eruptions of Taal in 1911, Hibok-hibok in 1951, and Pinatubo in 1991, this article interrogates Greg Bankoff's argument that "cultures of disaster" in the Philippines produce "coping mechanisms" manifested in public apathy and the state's failure at mitigation. It argues for historical contingency as illustrated by the relative success at disaster mitigation in Pinatubo's case, despite extreme challenges. It highlights the warning system in which the Aeta who lived on Mount Pinatubo, along with volcanologists and other key actors, played crucial roles. The Aeta's nonscientific perspective was not an obstacle to understanding risks and taking defensive action."